The Effect of Learning Experience Management by Using Games in Matific Application on the Development of Basic Mathematical Skills for Early Childhood Children in Kindergarten Year 1 - ทองแพง, ลัดดาวัลย์; คามะนา, จรรยา; หงษ์เจริญ, นารีรัตน์; แจ่มศรี, ไพโรจน์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to 1) develop basic mathematical skills of early childhood children in kindergarten year 1 by using games from Matific application according to the 75 percent criterion, and 2) study the progress of the development of basic mathematical skills of early childhood children in kindergarten year 1 by using games from Matific application. The sample group was 14 early childhood children in kindergarten year 1, class KG.1A at Sarasas Witaed Samutsakhon School. The research instruments were 1) 5 educational game activity experience plans with the  appropriate mean between 3.61-4.17, which was at a very appropriate level, and 2) a 20-item basic mathematical skills test with the difficulty index between 0.50-0.73, a discrimination index between 0.21-0.63, and a reliability value of 0.80. The statistics used for data analysis were percentages and relative development scores.          The research results found that 1) after learning with games from Matific application, the overall percentage of the basic mathematical skills assessment scores was 82.86 points, with 64.29 percent of early childhood children passing the 75 percent criterion and 35.71 percent failing the criterion, and 2) the early childhood children who learned by using games from Matific application had higher scores after learning, with an average high score for basic mathematical skills development, with a relative development score of 65.22.